Serological and infection statuses of dogs from a visceral leishmaniasis-endemic area - Laranjeira,Daniela Farias (2014)
OBJECTIVE This study investigated the serological status of dogs living in a visceral leishmaniasis-endemic area and its correlation with the parasitological condition of the animals.METHODS Canine humoral response was evaluated using the sera of 134 dogs by enzyme-linked immunosorbent assay and immunohistochemistry to detect parasites in the skin, lymph node, and spleen of the animals. The specific antibodies investigated were IgG, IgG1, IgG2, and IgE.RESULTS According to the parasitological, laboratory, and clinical findings, the dogs were placed into one of four groups: asymptomatic with (AP+, n = 21) or without (AP-, n = 36) Leishmania tissue parasitism and symptomatic with (SP+, n = 52) or without (SP-, n = 25) parasitism. Higher IgG and IgE levels were positively correlated with the infection condition and parasite load, but not with the clinical status. In all groups, total IgG was the predominant antibody, which occurred at the expense of IgG2 instead of IgG1. Most of the infected dogs tested positive for IgG (SP+, 98.1%; AP+, 95.2%), whereas this was not observed with IgE (SP+, 80.8%; AP+, 71.2%). The most relevant finding was the high positivity of the uninfected dogs for Leishmania-specific IgG (SP-, 60.0%; AP-, 44.4%), IgE (SP-, 44.0%; AP-, 27.8%), IgG1 (SP-, 28.0%; AP-, 22.2%), and IgG2 antibodies (SP-, 56.0%; AP-, 41.7%).CONCLUSIONS The serological status of dogs, as determined by any class or subclass of antibodies, did not accurately distinguish dogs infected with L. (L.) infantum chagasifrom uninfected animals. The inaccuracy of the serological result may impair not only the diagnosis, but also epidemiological investigations and strategies for visceral leishmaniasis control. This complex serological scenario occurring in a visceral leishmaniasis-endemic area highlights the challenges associated with canine diagnosis and points out the difficulties experienced by veterinary clinicians and coordinators of control programs.